2022
DOI: 10.1186/s12913-022-08116-w
|View full text |Cite
|
Sign up to set email alerts
|

The association between stress attributed to information systems and the experience of workplace aggression: a cross-sectional survey study among Finnish physicians

Abstract: Background Physicians commonly suffer from workplace aggression and its negative consequences. Previous studies have shown that stressors such as job demands increase the risk of inappropriate treatment at workplace. Poorly functioning, and constantly changing information systems form a major work stressor for physicians. The current study examined the association between physicians’ stress attributed to information systems (SAIS) and their experiences of workplace aggression. Workplace aggress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Not all studies were aimed at assessing workplace violence based on gender; therefore, we included all studies that either provided data on gender-based workplace violence or findings that indicated gender was a factor for WPV or a predictor for various outcomes of WPV. The latter group of studies had various aims, including: to assess factors associated with workplace violence [ 19 , 27 33 , 139 , 204 207 , 243 ], to assess the association between aggression, psychological distress, and job satisfaction [ 34 , 35 , 120 , 187 ], to determine injuries resulting from physical assaults [ 203 ], to determine the relationship between WPV and psychological and behavioral responses [ 35 37 , 161 , 200 , 202 , 208 211 ], to assess effects of lateral violence and its consequences [ 38 , 212 ], and to assess the preparedness to respond to sexual harassment before and after a workshop [ 39 , 65 ]. In addition to gender as the basis for WPV, we classified other factors associated with WPV that were not explicitly gendered, such as age and status (presented below).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Not all studies were aimed at assessing workplace violence based on gender; therefore, we included all studies that either provided data on gender-based workplace violence or findings that indicated gender was a factor for WPV or a predictor for various outcomes of WPV. The latter group of studies had various aims, including: to assess factors associated with workplace violence [ 19 , 27 33 , 139 , 204 207 , 243 ], to assess the association between aggression, psychological distress, and job satisfaction [ 34 , 35 , 120 , 187 ], to determine injuries resulting from physical assaults [ 203 ], to determine the relationship between WPV and psychological and behavioral responses [ 35 37 , 161 , 200 , 202 , 208 211 ], to assess effects of lateral violence and its consequences [ 38 , 212 ], and to assess the preparedness to respond to sexual harassment before and after a workshop [ 39 , 65 ]. In addition to gender as the basis for WPV, we classified other factors associated with WPV that were not explicitly gendered, such as age and status (presented below).…”
Section: Resultsmentioning
confidence: 99%
“…Younger age was found to be a significant risk factor for violence by several studies for both male and female healthcare providers [ 7 , 12 , 14 , 33 , 35 , 36 , 47 50 , 73 , 76 , 78 , 83 , 89 , 91 , 92 , 96 , 98 , 103 , 123 , 139 , 141 , 147 , 152 , 165 , 190 , 195 , 198 , 219 , 224 ]. The studies that reported a higher prevalence of WPV in general for women also reported that the younger age of the health care provider was associated with a higher risk of violence in various contexts, including verbal abuse [ 14 , 36 , 83 , 92 , 98 , 123 , 204 , 219 ], bullying, or mobbing [ 14 , 47 , 50 , 73 , 165 , 226 ], sexual harassment [ 12 , 36 , 44 , 49 , 78 , 152 , 224 ] and aggress...…”
Section: Resultsmentioning
confidence: 99%
“…First, organizational policies of cultural reforms particularly in the context of reducing worker-to-worker aggression and violence are required 111 . Second, organizational allocation of sufficient physician manpower to understaffed workplace is required to prevent understaffing-related excessive job demands and workplace aggression/violence 112 , 113 . Third, organizational-level prompt intervention of workplace violence occurrence by running of simulation-based behavioral training 114 and operating of behavioral emergency response teams 115 are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Workplace violence against medical personnel has a negative effect on workers mental health, exert psychological pressure on them, and can result in workplace absenteeism, job resignation ( 5 8 ). Workplace violence is complex problem which can impact different practitioners and can be caused by various risk factors including, high demand for health services, shortages of HCWs, long waiting times for health services, limited interpersonal trust, unrealistic patient expectations, and medical errors ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%